PENGARUH INVESTASI, INFLASI, SUKU BUNGA DAN TINGKAT UPAH TERHADAP PENYERAPAN TENAGA KERJA DI SEKTOR PERTANIAN PROPINSI SUMATERA UTARA - Kiagus Muhammad Zain Basriwijaya, Hamdi Sari Maryoni (Jurnal Ilmiah Cano Ekonomos, 2015)
This study aims: 1) to determine the basis of the leading sectors in North Sumatera,2) to determine an employment in the basis of sectors in North Sumatera, 3) to determinethe effect of investment, inflation, interest rates, and wages to the agricultural employmentin North Sumatera. To determine the basis of the leading sectors was conducted usinganalysis of Location Question (LQ). The effect of the investment, inflation, interest rates,and wages to agricultural employment in North Sumatera were analyzed by multiple linearregression analysis. The results of the research; 1) The basis sector in North Sumatera are;agriculture, construction, trade, transportation, and services sector, 2) basis labor sector inNorth Sumatera are agricultural transportation sector, 3) wages and investments have anegative significant to agricultural employment in North Sumatera.